Physiological and biochemical responses of durum wheat under mild terminal drought stress - Niari Khamssi, Nahid; Najaphy, Abdollah (Cellular and Molecular Biology, 2018)
The effects of mild terminal drought stress on physiological parameters and activities of peroxidase (POX), catalase (CAT) and superoxide dismutase (SOD) were investigated in ten durum wheat genotypes using two field experiments under rain-fed (terminal drought stress) and irrigated (non-stress) conditions. Stress intensity was calculated to be 0.1 indicating mild water deficit stress. Based on combined analysis of variance, the mild terminal drought stress increased the activity of CAT while, POX and SOD content decreased significantly. Rain-fed durum wheat plants showed non-significant increases in photochemical efficiency of PS II (Fv/Fm) as compared to the irrigated plants. Chlorophyll concentration in the flag leaves of the plants under terminal drought decreased slightly than normal conditions. The interaction of cultivar and environment was significant for enzyme activities, indicating different biochemical reaction of durum wheat plants in the two conditions.